2019
DOI: 10.1101/2019.12.15.876912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse genetic origins of medieval steppe nomad conquerors

Abstract: Over millennia, steppe nomadic tribes raided and sometimes overran settled Eurasian civilizations. Most polities formed by steppe nomads were ephemeral, making it difficult to ascertain their genetic roots or what present-day populations, if any, have descended from them. Exceptionally, the Khazar Khaganate controlled the trade artery between the Black and Caspian Seas in VIII-IX centuries, acting as one of the major conduits between East and West. However, the genetic identity of the ruling elite within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 56 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Following Klyosov and Faleeva (2017) who sequenced the first Y chromosomes of the Khazar, Mikheyev et al (2019) have pioneered the first ancient genome study of nine Khazar samples deemed to belong to upper (warrior) class. We have shown that consistently throughout their study Mikheyev et al (2019) carried out experiments and analyses that are inconsistent with the standards in Paleogenomics and population genetics. We questioned the authors' choice of analyses, populations, and markers and demonstrated that the authors' analyses are biased and lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following Klyosov and Faleeva (2017) who sequenced the first Y chromosomes of the Khazar, Mikheyev et al (2019) have pioneered the first ancient genome study of nine Khazar samples deemed to belong to upper (warrior) class. We have shown that consistently throughout their study Mikheyev et al (2019) carried out experiments and analyses that are inconsistent with the standards in Paleogenomics and population genetics. We questioned the authors' choice of analyses, populations, and markers and demonstrated that the authors' analyses are biased and lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…A further curiosity concerns the author's emphasis on demonstrating the correlation between genetics and geography in their samples and their results for Ashkenazic Jews. Their analyses (Mikheyev et al (2019) Figure 1A) shows that Ashkenazic Jews cluster with North Ossetia and Caucasus populations, rather than their neighboring communities. It is difficult to reconcile this finding with the authors' beliefs that the high genetic-geographic correlation makes their populations "strongly informative about the geographic origins of the Khazars" and their criticism towards past studies that showed a Caucasus origin for Ashkenazic Jews (Das et al 2016;Das et al 2017).…”
Section: Choice Of the Reference Datasetmentioning
confidence: 98%
See 3 more Smart Citations